Empowering Rural Communities in Pakistan through AI and Digital Literacy: A Pathway to Inclusive Growth and Sustainable Development - Abul, Hassan; Adeel, Anwar; Ali Ab, Ul Hassan (INTI International University, 2026)
Rural communities in Pakistan are facing significant challenges in accessing quality education and economic opportunities. The main reason for these barriers is geographical isolation and limited infrastructure. Digital technologies have the potential to bridge such gaps. However, there is minimal research on how AI literacy and digital learning tools can assist. These tools can transform the educational and economic prospects of these areas. This study intends to examine the role of AI and digital literacy in empowering rural communities, specifically through e-commerce and freelancing. The objective of this study is to investigate how AI and digital literacy contribute to the empowerment, and to examine how technologies foster economic growth and sustainable development in rural areas of Pakistan. A qualitative approach is used, utilizing interviews and discourse analysis to gather insights from rural learners, educators, and entrepreneurs. A semi-structured interview was used, and the data were analyzed thematically. The findings suggest that AI-driven and digital platforms are acting as informal teachers. They are offering accessible and low-cost education. Thus, indirectly helping rural communities to participate in the digital economy. These technologies are also reducing the urban-rural divide by improving livelihoods. The study is novel because of its focus on how AI literacy and digital learning are breaking traditional education barriers. It also shows how rural communities are joining global freelancing markets. This research highlighted the potential of digital tools in promoting inclusive growth. These are also essential to address the economic inequalities in rural Pakistan.